2004
DOI: 10.4049/jimmunol.172.7.4253
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells Regulate Th Cell Responses through OX40 Ligand and Type I IFNs

Abstract: Dendritic cells (DCs) show a functional plasticity in determining Th responses depending on their maturational stage or on maturational signals delivered to the DCs. Human plasmacytoid DCs (PDCs) can induce either Th1- or Th2-type immune responses upon exposure to viruses or IL-3, respectively. In this study we have investigated the Th-polarizing capacity of PDCs after short (24-h) or long (72-h) culture with stimuli and have assessed the expression and function of OX40 ligand (OX40L) in PDC-mediated Th polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
122
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 45 publications
8
122
0
Order By: Relevance
“…TNFRSF4 and its ligand, TNFS4, have been reported to inhibit apoptosis in T cells and to enhance Th2 proliferation. 2,27 However, some infectious agents may also induce Th1 proliferation through TNFRSF4 signals. 22,28 In the context of allergy, however, recall responses were shown to be dependent on TNFRSF4 signals in an animal model of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…TNFRSF4 and its ligand, TNFS4, have been reported to inhibit apoptosis in T cells and to enhance Th2 proliferation. 2,27 However, some infectious agents may also induce Th1 proliferation through TNFRSF4 signals. 22,28 In the context of allergy, however, recall responses were shown to be dependent on TNFRSF4 signals in an animal model of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PDC express OX40L upon stimulation, and that virus-stimulated PDC modulate Th responses via OX40L and IFN-a [60]. However, involvement of OX40L in PDC-mediated activation of NKT cells or CD8 T cells has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo function of pDCs as APCs remains controversial and functional outcomes of pDC-T cell interactions largely depend on the immunological context of the encounter (47). Activated pDCs have been demonstrated to promote Th1 (31,47) as well as Th2 responses (32,33), underlining their remarkable functional plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Activated pDCs have been demonstrated to promote Th1 (31,47) as well as Th2 responses (32,33), underlining their remarkable functional plasticity. The pDCs were shown to prime specific CD4 + and CD8 + lymphocytes against endogenous and exogenous Ags (15,48), viruses (49) and tumor Ags (45).…”
Section: Discussionmentioning
confidence: 99%